Developing knowledgeable patin farmers in Temerloh, Pahang - Abd Rahman, Nordin; Christianus, Annie; Saad, Che Roos; Mohd Daud, Hassan; Man, Norsida; Abd Rahim, Abdullah; Kamaruzaman, Ahmad Dahari; A. Manan, Junainah; Mohd Nor, Nik Muhamad Adnan; A. Rahman, Saiful Anuar; Ramli, Noor Azwani; R. R., Siti (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Patin Fish or locally known as `ikan patin’ is quite a common and popular fish within some other Southeast Asian countries such as Cambodia, Vietnam, Burma, Thailand, Indonesia and in America too (top 10 consumed). Patin or Pangasius farming is said to have started in Malaysia in the early 1980’s to help the development of the aquaculture sector in the country, as the local river patin is becoming scarce. Temerloh, a small town in Pahang where the famous Pahang River flows is synonym with patin, and the special dish of `patin tempoyak’ has been declared as Bandar Patin (Patin Town) since 1990. However the patin production in Temerloh has been very limited and inconsistent and could not cater even the local demand, while some patin farmers are closing down for so many reasons. Understanding the specialty of patin to Temerloh and its potential to be upgraded into a more dynamic industry, thus a group of expertise with multi-disciplinary background from Universiti Putra Malaysia (UPM) and supported by the KTP funding initiated a special program to help train the patin farmers to become more knowledgeable in their patin farming and introducing them to the diverse patin downstream industries. Knowledge transfer activities were organized with problem solving approach including netted -pond good management practice, disease management, fish-feed formulation, and others. This project is hopes to be impactful to the patin farmers and empowering them to be successful entrepreneurs, while making Temerloh a real patin town.